2017
DOI: 10.1364/oe.25.016378
|View full text |Cite
|
Sign up to set email alerts
|

Gamut Volume Index: a color preference metric based on meta-analysis and optimized colour samples

Abstract: A novel metric named Gamut Volume Index (GVI) is proposed for evaluating the colour preference of lighting. This metric is based on the absolute gamut volume of optimized colour samples. The optimal colour set of the proposed metric was obtained by optimizing the weighted average correlation between the metric predictions and the subjective ratings for 8 psychophysical studies. The performance of 20 typical colour metrics was also investigated, which included colour difference based metrics, gamut based metric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…According to the current literature, the whiteness of lighting [1][2][3][4][5][6][7] and colour preference for lighting [8][9][10][11][12][13][14][15][16][17][18][19][20] are two of the most popular issues when evaluating the colour quality of light sources. Anecdotally, people prefer white illumination for general lighting applications although in some countries, some people are said to prefer yellowish lighting at home in the living room for relaxing in the evening.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the current literature, the whiteness of lighting [1][2][3][4][5][6][7] and colour preference for lighting [8][9][10][11][12][13][14][15][16][17][18][19][20] are two of the most popular issues when evaluating the colour quality of light sources. Anecdotally, people prefer white illumination for general lighting applications although in some countries, some people are said to prefer yellowish lighting at home in the living room for relaxing in the evening.…”
Section: Introductionmentioning
confidence: 99%
“…34 In addition, an objective measure for such a colour quality dimension is also urgently desired. 9,10,12,13,17,18,35 In 2013, a relevant study that considered the correlation between colour preference and the whiteness of lighting was implemented by Rea and Freyssinier. 2 Their results indicated that people preferred whiter illumination for indoor applications.…”
Section: Introductionmentioning
confidence: 99%
“…However, the reverse is found not to be the case. Therefore, we separately select highly-saturated samples at the color gamut boundary of the printing color atlas [8], [20].…”
Section: Evaluation Methods Based On the Optimization Of Tcs A Wmentioning
confidence: 99%
“…Therefore, special consideration needs to be given to the effect of highly-saturated samples on the model. The color atlas samples are classified as highly-saturated sample set g at the color gamut boundary and the set f in the color gamut [17], [20].…”
Section: Evaluation Methods Based On the Optimization Of Tcs A Wmentioning
confidence: 99%
See 1 more Smart Citation